1957
DOI: 10.1007/bf02640261
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of alkylated phenols as antioxidants for lard

Abstract: Summary Tests with 24 substituted phenols showed that position was more important than the nature of the alkyl group in influencing antioxidant potency for lard. The most active compound tested was 2,6‐di‐tert‐butyl‐4‐methylphenol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

1962
1962
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 4 publications
0
11
0
1
Order By: Relevance
“…Gorden (1990) reported that substitution at the para position with an ethyl or n-butyl group rather than a methyl group improves the activity of the antioxidant; however, the presence of chain or branched alkyl groups in this position decreases the antioxidant activity. The stability of the phenoxyl radical is further increased by bulky groups in the 2 and 6 positions as in 2,6-di-t-butyl-4-methylphenol (BHT) (Miller & Quakenbush, 1957), since these substituents increase the steric hindrance in the region of the radical and thereby further reduce the rate of propagation reactions involving the antioxidant radical (Reactions 8,9,10 …”
Section: R Ro Roo Ahmentioning
confidence: 99%
“…Gorden (1990) reported that substitution at the para position with an ethyl or n-butyl group rather than a methyl group improves the activity of the antioxidant; however, the presence of chain or branched alkyl groups in this position decreases the antioxidant activity. The stability of the phenoxyl radical is further increased by bulky groups in the 2 and 6 positions as in 2,6-di-t-butyl-4-methylphenol (BHT) (Miller & Quakenbush, 1957), since these substituents increase the steric hindrance in the region of the radical and thereby further reduce the rate of propagation reactions involving the antioxidant radical (Reactions 8,9,10 …”
Section: R Ro Roo Ahmentioning
confidence: 99%
“…However, a decrease in the antioxidant activity was due to the presence of alkyl chain or branched alkyl groups on para position. When bulky groups are present at 2 and 6 positions, the stability of radicals of an aromatic ring is additionally increased as shown in butylated hydroxytoluene (BHT) (Miller & Quackenbush, 1957). The bulky groups contribute to the steric hindrance in the radical region, thus, reducing the rate of propagation reactions of free radicals.…”
Section: Hydrogen Atom Transfermentioning
confidence: 99%
“…When the relative activities of monoalkyl derivatives of monohydric phenols (Type VII, Table III) in isotactic polypropylene were compared, substitution at the ortho position was more advantageous than at the para position. Further, in the series of dialkyl derivatives of monohydric phenols higher activity is displayed in glycerides of fatty acids (19) by antioxidants substituted in positions 2,6-i.e., in both posi tions ortho to the hydroxylic group. On the contrary, in gasoline (37) 2,4-dialkylphenols were more active; this points out the different impor tance of substitution in both ortho and para positions in different substrates.…”
Section: ) For 4-alkylpyrocatecholsmentioning
confidence: 99%